1990
DOI: 10.1111/j.1469-8137.1990.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular‐arbuscular mycorrhizas and the soil‐disturbance‐induced reduction of nutrient absorption in maize.

Abstract: SUMM.4RYMaize seedlings have been show-n to absorb more phosphorus (P) from soil from long term zero-til! plots than from the same soil after disturbance, apparently because of greater vesicular-arbuscular (VA) mycorrhizal colonization m the undisturbed soil. A growth room experiment was conducted to determine the effect of soil P availability on this phenomenon. Maize was grown for three 3-week cycles in initially disturbed soil. Phosphorus was mixed with tbe soil to create five P-amendment rates: 0, 40, 80, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 20 publications
1
18
2
Order By: Relevance
“…Phosphorus fertilization does not always reduce mycorrhizal association. In studies reviewed by Miller et al (1995), extensive mycorrhizal colonization was observed even at very high rates of fertilization (Fairchild and Miller 1988). Localized concentration of P in fertilized systems could also influence mycorrhizal activity.…”
Section: Impact Of Phosphorus Application and Other Nutrientsmentioning
confidence: 99%
“…Phosphorus fertilization does not always reduce mycorrhizal association. In studies reviewed by Miller et al (1995), extensive mycorrhizal colonization was observed even at very high rates of fertilization (Fairchild and Miller 1988). Localized concentration of P in fertilized systems could also influence mycorrhizal activity.…”
Section: Impact Of Phosphorus Application and Other Nutrientsmentioning
confidence: 99%
“…In addition, elimination of AM by either irradiation or application of a fungicide minimized the effect of disturbance (Evans and Miller 1988). Fairchild and Miller (1988) found that the manifestation of the effect did not require an extended period without disturbance. They began with disturbed soil and grew maize in a growth room for four cycles of 3-wk each, disturbing half the pots after each cycle.…”
Section: Discovery Of the Effectmentioning
confidence: 99%
“…Thus, the sym pathway is known to involve the perception of putative Myc or Nod factors by a receptor kinase (SYMRK; MtDM2 in Medicago truncatula), 57 followed by the presumed release of a plastidic factor via a putative plastid-localized ion channel (MtDM1), the involvement of a nucleoporin protein sharing homology with a component of the nuclear pore complex, and, ultimately, a down-stream induction of nuclear calcium signal spiking thought to be detected by a calcium-and calmodulin-dependent protein kinase (CCaMK; MtDM3), which leads to the induction of the complex genetic and metabolic re-programming required for the symbiosis. 31 An growth 26,27 or when the symbiosis-specific phosphate uptake mechanism of the plant is disrupted to such an extent that it prevents nutrient acquisition. 28,29 Signaling in the AM Symbiosis: New Messages From the Underground A plethora of experimental findings by diverse groups has dispelled some of the aura of mystery that still surrounds the mechanisms that lead to the establishment of the AM symbiosis.…”
Section: The Arbuscular Mycorrhizal Symbiosis: An Ancient Friendship mentioning
confidence: 99%